Preserving and conserving Kampung Baru as a malay heritage in Kuala Lumpur / Maisarah Ishak and Sharifah Zannierah Syed Marzuki - Ishak, Maisarah; Syed Marzuki, Sharifah Zannierah (2015)
An urban village located in the heart of Kuala Lumpur, Kampung Baru was established by the British Government since 1899. It was managed by the Malay Agricultural Settlement (M.A.S.) that took care of the village's affairs and the needs of the residents. Kampung Baru was also gazetted as one of the Malay Reserved Areas (MRA) and created under the Malay Reservation Enactment of 1913 and the Land Enactment of 1987. Since then, Kampung Baru has witnessed major developments of the capital city of Malaysia with skyscrapers that surrounded this urban village. Some of the initiatives inspired by the Government to modernize the area have been welcomed by some quarters but there are others who remain silence and skeptical regarding the development plans. Kampung Baru is moving towards a new dimension whilst preserving and conserving it as a Malay and national heritage.